2023
DOI: 10.3390/pharmaceutics15082066
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Modification Techniques for Natural Polymer-Based Drug Delivery Systems

Pankaj Bhatt,
Vipin Kumar,
Vetriselvan Subramaniyan
et al.

Abstract: Natural polymers have attracted significant attention in drug delivery applications due to their biocompatibility, biodegradability, and versatility. However, their surface properties often limit their use as drug delivery vehicles, as they may exhibit poor wettability, weak adhesion, and inadequate drug loading and release. Plasma treatment is a promising surface modification technique that can overcome these limitations by introducing various functional groups onto the natural polymer surface, thus enhancing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 166 publications
0
6
0
Order By: Relevance
“…Evidence from this study indicates that this methodology not only facilitates sustained EGCG release but also simulates a proteolytic environment akin to physiological conditions, potentially elevating the therapeutic applica-bility of PG matrices in mitigating oxidative stress-related cellular damage. In addition, this research expands the possibilities for EGCG delivery systems and emphasizes the importance of convenient and cost-effective drug-delivery methods in current and future pharmaceutical research [18,19].…”
Section: Discussionmentioning
confidence: 92%
“…Evidence from this study indicates that this methodology not only facilitates sustained EGCG release but also simulates a proteolytic environment akin to physiological conditions, potentially elevating the therapeutic applica-bility of PG matrices in mitigating oxidative stress-related cellular damage. In addition, this research expands the possibilities for EGCG delivery systems and emphasizes the importance of convenient and cost-effective drug-delivery methods in current and future pharmaceutical research [18,19].…”
Section: Discussionmentioning
confidence: 92%
“…To overcome this challenge and improve the versatility of polymeric materials in applications that require adhesive bonding, various surface modification techniques are commonly employed. Numerous studies have shown that plasma treatments are some of the most promising surface modification methods [ 9 , 10 ]. These techniques are capable of altering the physical and chemical properties of a material surface, thereby significantly enhancing the surface wettability and adhesion properties without influencing the bulk properties of the material [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This issue is not only of academic [ 3 , 5 , 6 , 7 , 8 , 9 ], but also of direct applied interest. In particular, the question of using polymers undergoing phase transitions to create drug delivery systems has been repeatedly raised in the literature [ 10 , 11 , 12 , 13 , 14 , 15 ]. It was also proposed to use phase transitions, which are expressed in in the form of sharp solution turbidity, for the creation of information display systems [ 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%